Effect of Elastomeric Nanoparticles on Polystyrene/Organic Nanocomposites - Sungwon Ma; Yonathan Thio (International Journal of Polymer Science)
The rheological behavior of nanosheet composites and the effect of morphology between elastomeric nanofiber and nanosheet composites were studied using a Cross-Williamson model and critical volume concentration was investigated by percolation threshold theory for fiber and sheet morphologies. Nanofiber and nanosheet particles were synthesized by a cold vulcanization process using a S2Cl2 cross-linking reagent resulting from self-assembly of a PS-PI block copolymer. Nanofiber and nanosheet characterization was done by SEM. Rheological properties were measured and analyzed in terms of varying nanofiller and nanosheet loading from 0.5 to 10 wt%. For the nanofiber and nanosheet composites, the moduli were increased with increasing filler loading, whereas moduli of SI23 and SI43 composite decreased with increasing content. Both nanofiber and nanosheet composites showed a nanosized filler effect and their structural changes were between 5 and 10 wt%. Cross-Williamson three-parameter model was used to find zero-shear viscosity and relaxation time. Percolation threshold theory was used to study structural changes and calculate values.